2015
DOI: 10.3171/2014.10.jns132713
|View full text |Cite
|
Sign up to set email alerts
|

The nonsurgical nature of patients with subarachnoid or intraparenchymal hemorrhage associated with mild traumatic brain injury

Abstract: Patients with the constellation of SAH and/or IPH and mTBI do not require neurosurgical consultation, and these findings should not be used as the sole criteria to justify transfer to tertiary referral centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…Joseph et al concluded, based on their data that ACS services can independently care for patients with mild TBI without obtaining a formal neurosurgical consultation given the rarity of neurosurgical consultation in this group 12. A recent study from Alabama concluded patients with mild TBI with isolated tSAH or intraparenchymal hemorrhage should not require a neurosurgical consultation or even transfer to a major center 7. In a retrospective study specifically looking at isolated tSAH, Phelan et al concluded that these injuries are less severe brain injuries than other TBI and those with GCS scores of 13–15 demonstrate low rates of clinical progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Joseph et al concluded, based on their data that ACS services can independently care for patients with mild TBI without obtaining a formal neurosurgical consultation given the rarity of neurosurgical consultation in this group 12. A recent study from Alabama concluded patients with mild TBI with isolated tSAH or intraparenchymal hemorrhage should not require a neurosurgical consultation or even transfer to a major center 7. In a retrospective study specifically looking at isolated tSAH, Phelan et al concluded that these injuries are less severe brain injuries than other TBI and those with GCS scores of 13–15 demonstrate low rates of clinical progression.…”
Section: Discussionmentioning
confidence: 99%
“…A more selective approach has been proposed, with repeat studies in patients with deterioration in their Glasgow Coma Score (GCS) 4 5. The need for a mandatory neurosurgery consultation has also been questioned 6 7…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to those patients with tSAH in the presence of other intracranial hemorrhage, the prognosis of patients with isolated tSAH is good [ 9 , 10 ]. In patients with mild TBI (Glasgow Coma Scale (GCS) score ≥13) and isolated tSAH, no neurologic decline or need for neurosurgical procedures was observed [ 11 , 12 , 13 , 14 , 15 ]. In a retrospective study evaluating isolated tSAH in patients with mild TBI (GCS 13–15), of 67 patients, only 1 patient (1.5%) experienced neurological deterioration, and not a single patient required neurosurgical intervention [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although a change in GCS score is used to identify neurological deterioration, which is often an indication for a neurosurgical intervention, admission GCS score has been repeatedly shown to be a poor determinant of subsequent neurosurgical intervention; our study lends support to this conclusion. 3,27,36 This reoccurring observation should not be unexpected because the GCS was designed to reflect differences in the risk for mortality, not neurosurgical intervention. When we examined the interaction of GCS score and hemorrhage thickness in a multivariable logistic regression model, the odds of neurosurgical intervention for each millimeter increase in hemorrhage thickness was similar for each admission GCS group (p-interaction 0.19).…”
Section: Discussionmentioning
confidence: 97%
“…A question repeatedly posed in the TBI literature is whether a neurosurgical consultation, or a requirement for neurosurgical coverage, is necessary for all patients with an mTBI and ICH. 2,3,8,11,14,17,36 Unfortunately, we do not have enough of an understanding of the risk for neurosurgical intervention to create management guidelines addressing particular ICH types in patients with mTBI. 9 In order to better understand the risk, we must collect detailed information about each injury and assess the influence of each variable on the risk of neurosurgical intervention through predictive modeling.…”
mentioning
confidence: 99%